PENGUKURAN KINERJA DINAS KELAUTAN DAN PERIKANAN KABUPATEN SITUBONDO - Suroso, Imam; Rudyanto, Tomy; Sulistiyo, Agung Budi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: Performance measurement is critical for public sector organizations to determine the sucess level in implementing strategies to achieve its vision and mission. Therefore, an analytical tool is needed to measure government performance and to provide comprehensive information from both financial and non-financial aspects. The use of balanced scorecard as the measurement method could broaden the perspective, not only from the financial perspective, but also from the customer, internal business processes, and learning and growth perspectives. The objective of this study was to analyze the performance of the Department of Marine and Fisheries of Situbondo Regency in 2015 using a balanced scorecard approach. This was a descriptive qualitative research applying a case study. The informants were the local people and staffs of the Department of Marine and Fisheries of Situbondo Regency. Value for money analysis was used in measuring financial perspective and service quality (servqual), while Important Performance Analysis (IPA) used in measuring other perspectives. Conclusion was drawn based on the scoring results. Results showed that, in overall, the performance of the Department of Marine and Fisheries of Situbondo Regency was in â€œgoodâ€ category. Results of servqual analysis showed that all aspects had negative values, meaning that the expectations were higher than perceptions so the performance should be improved based on the priorities indicated in the IPA analysis. Keywords: Performance Measurement, Balanced Scorecard.